After the epidemic: Zika virus projections for Latin America and the Caribbean. - Felipe J Colón-González; Carlos A Peres; Christine Steiner São Bernardo; Paul R Hunter; Iain R Lake (PLoS Neglected Tropical Diseases, 2017)
Zika is one of the most challenging emergent vector-borne diseases, yet its future public health impact remains unclear. Zika was of little public health concern until recent reports of its association with congenital syndromes. By 3 August 2017 ∼217,000 Zika cases and ∼3,400 cases of associated congenital syndrome were reported in Latin America and the Caribbean. Some modelling exercises suggest that Zika virus infection could become endemic in agreement with recent declarations from the The World Health Organisation.We produced high-resolution spatially-explicit projections of Zika cases, associated congenital syndromes and monetary costs for Latin America and the Caribbean now that the epidemic phase of the disease appears to be over. In contrast to previous studies which have adopted a modelling approach to map Zika potential, we project case numbers using a statistical approach based upon reported dengue case data as a Zika surrogate. Our results indicate that ∼12.3 (0.7-162.3) million Zika cases could be expected across Latin America and the Caribbean every year, leading to ∼64.4 (0.2-5159.3) thousand cases of Guillain-Barré syndrome and ∼4.7 (0.0-116.3) thousand cases of microcephaly. The economic burden of these neurological sequelae are estimated to be USD ∼2.3 (USD 0-159.3) billion per annum.Zika is likely to have significant public health consequences across Latin America and the Caribbean in years to come. Our projections inform regional and federal health authorities, offering an opportunity to adapt to this public health challenge.